Gestational Diabetes Mellitus (GDM): Effects on pregnancy, delivery and long-term health outcomes in mothers and offspring - Kaczmarek , Aleksandra; Kaczmarek , Wojciech; Krakowiak, Magdalena; Gołacki, Rafał; Jabłonowska, Magdalena; Bagiński, Konrad (Quality in Sport, 2025)
Introduction: Gestational Diabetes Mellitus (GDM) is conventionally defined as any degree of glucose intolerance with onset or first recognition during pregnancy [1]. GDM has been consistently associated with a spectrum of adverse obstetric and neonatal outcomes [2]. The purpose of this study was to evaluate the effects of Gestational Diabetes Mellitus (GDM) on maternal and neonatal outcomes during pregnancy and delivery, and its long-term effects on both mothers and their offspring’s health. Materials and methods: A review of chosen literature in the PubMed database was conducted, using the following key words: , diabetes”, , gestational diabetes mellitus’’, , glucose intolerance’’, , macrosomia’’, , perinatal complications’’ Summary: Gestational Diabetes Mellitus (GDM) is among the most common metabolic disorders of pregnancy and is linked to multiple adverse maternal and neonatal outcomes. Risk factors of developing gestational diabetes were taken into consideration, as well as a pathophysiological mechanism of gestational diabetes was examined in order to elaborate on the short-range and long-range consequences for both mothers and their offspring [3]. Furthermore, diagnosis of GDM, medical treatment and prevention of its effects were also discussed in this study. Conclusion: Recognition of GDM impact on the course of pregnancy, delivery, and their outcomes and identifying it as an important predictor of long-term cardiometabolic risk of both mothers and their offspring, what is crucial for optimizing care and planning strategies of medical interventions [4].